2020
DOI: 10.2478/raon-2020-0054
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-lymphocyte ratio can predict outcome in extensive-stage small cell lung cancer

Abstract: BackgroundThe neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and lymphocyte-to-monocyte ratio (LMR) were analyzed in various carcinomas and their potential prognostic significance was determined. The objective of present study was to determine the correlation between these parameters and the survival of patients with small cell lung cancer (SCLC), since very few studies have been published on this type of carcinoma.Patients and methodsOne hundred and forty patients diagnosed with SCL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 56 publications
(81 reference statements)
1
14
0
Order By: Relevance
“…We confirm previous reports that show SI is a poor prognostic indicator in NSCLC [ 10 , 35 , 36 ]. However, high IL-6 levels are also known to be a poor prognostic indicator in NSCLC, but we did not find a significant direct linear relationship between IL-6 and NLR values in our cohort [ 20 , 21 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We confirm previous reports that show SI is a poor prognostic indicator in NSCLC [ 10 , 35 , 36 ]. However, high IL-6 levels are also known to be a poor prognostic indicator in NSCLC, but we did not find a significant direct linear relationship between IL-6 and NLR values in our cohort [ 20 , 21 ].…”
Section: Discussionsupporting
confidence: 92%
“…None of SI marker were associated with PFS in SCLC patients. While there are some reports that show a relationship between SI markers and PFS or overall survival (OS) in SCLC [ 10 , 12 , 17 ], others fail to establish an association in this type of disease, which may be a result of suboptimal values to define SI [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in our patient data, no relationship between either absolute neutrophil or leucocyte count alone was found to be significantly associated with the prognosis. NLR has been reported as a potential prognostic marker, and the elevated ratio is associated with poor prognosis of different cancers such as breast cancer [13], gastric cancer [14,15], advanced melanoma treated with nivolumab [16], pancreatic cancer [17], and in extensive-stage small cell lung cancer [18]. However, due to the heterogenicity of patient populations, the relationship needs to be analyzed for different patient populations to develop a cut-off that is best fit for specific patient groups (or at least large patient groups), because neutrophil and lymphocyte may vary in response to many factors, including treatment protocols, drugs, and methods.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils in human peripheral blood have the functions of phagocytosis, chemotaxis, and bactericide, and lymphocytes are involved in the immune response [10,11]. Studies have shown that the normal NLR values in an adult, nongeriatric, population in good health are between 0.78 and 3.53 [12], neutrophil-to-lymphocyte ratio (NLR) has a potential as prognostic marker, and the elevated NLR is associated with poor prognosis of diseases and cancers such as breast cancer [13], gastric cancer [14,15], advanced melanoma treated with nivolumab [16], pancreatic cancer [17], in extensive-stage small cell lung cancer [18], and others [19,20]. However, it is unknown whether if it has prognostic value for HCC patients after interventional therapies.…”
Section: Introductionmentioning
confidence: 99%
“… 7 Recently accumulated evidence indicates that inflammation is an important factor affecting patients’ responses to treatment and prognosis. A series of blood-based markers, including the neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR), have been reported to be effective for predicting patients’ survival in various cancers, 8 10 including NSCLC. 11 Blood coagulation disorder is a common complication of malignant tumors, and recent studies demonstrated that coagulation system activation is associated with progression and metastasis in various cancers.…”
Section: Introductionmentioning
confidence: 99%